Method for aggregating correlated interval grey linguistic variables and its application to decision making - Zhang, Nian (Technological and Economic Development of Economy, 2013)
With respect to multiple attribute decision making (MADM) problems in which attribute values take the form of interval grey linguistic variables, a new decision making analysis method is developed. In this paper, we propose the interval grey linguistic variables ordered weighted aggregation (IGLOWA) operator, and then use the Choquet integral to develop the interval grey linguistic correlated ordered arithmetic aggregation (IGLCOA) operator and the interval grey linguistic correlated ordered geometric aggregation (IGLCOGA) operator. Those operators not only consider the importance of the elements, but also can reflect the correlations among the elements. Then, we develop an approach to multiple attribute decision making problems with correlative weights which attribute values are given in terms of interval grey linguistic variables information based on those operators. Finally an illustrative example is given to use the method in the range of uncertain multiple attribute decision making. The results show that the method proposed in this paper is feasible. First published online: 15 Mar 2013